(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article considers the problem of the spreading of the process of globalization, which was refl ected not only in the political and economic spheres of human life, but also directly touched the spiritual world of modern man. Political and economic achievements of the most developed countries hasn’t any infl uence, but their lifestyle is becoming a role model. The effect of other cultural samples on the mass consciousness can lead to be transformed by national moral values. The authors comprehensively considering this issue, offer their concluding ideas: no by denial of globalization, and the defi nition of its negative infl uence; not by negation of all the Western samples (Westernization), but by keeping the originality (identity) to establish a dialogue with the Western culture; identifying infl uence ways of the media on the formation of mass consciousness, to direct their activity on revival of a national idea. Key words: value, mass consciousness, national self-identity, globalization, national spirit, national idea.